HUBUNGAN PENDIDIKAN KESEHATAN TERHADAP PARTISIPASI SISWA DALAM MENJAGA KEBERSIHAN LINGKUNGAN SEKOLAH - ERFANANDA YULIO PRATIKTA, - (2019)
The focus of the problem in this research is the student understanding level of environmental health is quite good, but the students are not familiar with the activities that show their concern for the environment. To overcome for these problems,the students are taught health education and involved in maintaining the cleanliness of the school environment activities. The formulation problem in this research is how the relationship between health education to student participation in maintaining the cleanliness of the school environment (study at SMPN 1 Karangtanjung). The purpose of this researchis to know the relationship of health education to student patcipation in maintaining the cleasnliness of the school environment (Study at SMPN 1 Karangtanjung). The method used in this research is quantitative descriptive research. The Data collection is done through questionnaires. The subjects of the research are the student at class VII, wich amountedto 36 students. To analyze the research data used Pearson Correlation Tes. Based on data analysis health education to student participation in maintaining the cleanliness of the school environment, the sig value (0,552) > 0,05 was obtained. Based on data analysis, it can be concluded that there is a significant relationship between health education to student participation in maintaining the cleanliness of the school environment with the price of rxy = 0,552.